Treatment and education reduce the severity of schistosomiasis periportal fibrosis - Paula Carolina Valenca Silva; Tallita Verissimo Leal; Ana Lucia Coutinho Domingues (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Introduction This study evaluates the factors associated with the development of severe periportal fibrosis in patients with Schistosoma mansoni. Methods A cross-sectional study was conducted from April to December 2012 involving 178 patients infected with S. mansoni who were treated in the Hospital das Clínicas of Pernambuco, Brazil. Information regarding risk factors was obtained using a questionnaire. Based on the patients' epidemiological history, clinical examination, and upper abdomen ultrasound evaluation, patients were divided into 2 groups: 137 with evidence of severe periportal fibrosis and 41 patients without fibrosis or with mild or moderate periportal fibrosis. Univariate and multivariate analyses were conducted using EpiInfo software version 3.5.5. Results Illiterate individuals (30.1%) and patients who had more frequent contact with contaminated water in towns in the Zona da Mata of Pernambuco (33.2%) were at greater risk for severe periportal fibrosis. Based on multivariate analysis, it was determined that an education level of up to 11 years of study and specific prior treatment for schistosomiasis were preventive factors for severe periportal fibrosis. Conclusions The prevailing sites of the severe forms of periportal fibrosis are still within the Zona da Mata of Pernambuco, although there has been an expansion to urban areas and the state coast. Specific treatment and an increased level of education were identified as protective factors, indicating the need for implementing social, sanitary, and health education interventions aimed at schistosomiasis to combat the risk factors for this major public health problem.